2017
DOI: 10.1007/s00520-016-3558-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical research participation among adolescent and young adults at an NCI-designated Comprehensive Cancer Center and affiliated pediatric hospital

Abstract: Purpose Minimal clinical trial participation among adolescents and young adults (AYAs) with cancer limits scientific progress and ultimately their clinical care and outcomes. These analyses examine the current state of AYA clinical research participation at a Midwestern comprehensive cancer center and affiliated pediatric hospital to advise program development and increase availability of trials and AYA participation. Enrollment is examined across all diagnoses, the entire AYA age spectrum (15–39), and both ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 19 publications
2
48
0
Order By: Relevance
“…Although CCTs existed nationally for more than half of our AYAs at both sites, CCTs were available for only one third as many AYAs at the adult cancer hospital. Although the overall low CCT enrollment of about 10% at both sites was not unexpected and is consistent with previous reports, 1,8,13,17 our findings of national-level similarity in CCT existence, but site-level disparity in CCT availability, are novel. They are significant because they demonstrate the need to account for treatment setting when considering solutions for the difficult problem of low CCT enrollment of AYAs.…”
Section: Discussionsupporting
confidence: 92%
“…Although CCTs existed nationally for more than half of our AYAs at both sites, CCTs were available for only one third as many AYAs at the adult cancer hospital. Although the overall low CCT enrollment of about 10% at both sites was not unexpected and is consistent with previous reports, 1,8,13,17 our findings of national-level similarity in CCT existence, but site-level disparity in CCT availability, are novel. They are significant because they demonstrate the need to account for treatment setting when considering solutions for the difficult problem of low CCT enrollment of AYAs.…”
Section: Discussionsupporting
confidence: 92%
“…19 Sanford et al examined AYA enrollment onto clinical trials from 2010 to 2014 in affiliated pediatric and adult NCI-designated cancer centers, finding 11% of AYAs were enrolled in the adult setting while 42% were enrolled in the pediatric setting. 18 While our population-based study demonstrated higher overall clinical trial enrollment, as well as improvements over time, in the cancer types studied, the persistent issue of lower overall clinical trial enrollment relative to the pediatric populations remains. The relatively lower proportional enrollment of AYAs relative to other age groups was recently demonstrated in a study of clinical trial enrollment within the NCI’s CCOP.…”
Section: Discussionmentioning
confidence: 70%
“…5,11,13 Our findings are comparable to recently published studies of clinical trial enrollment among AYAs in single or affiliated institutions. 18 In a single-institution study, Collins et al found 6% of AYAs were enrolled on clinical trials from 2008-2012. 19 Sanford et al examined AYA enrollment onto clinical trials from 2010 to 2014 in affiliated pediatric and adult NCI-designated cancer centers, finding 11% of AYAs were enrolled in the adult setting while 42% were enrolled in the pediatric setting.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the same period, the enrollment onto therapeutic clinical trials from this study was comparable to that in other studies; in the United States, from 2009 to 2013, 21 the proportion of AYA enrollments was 29% in therapeutic studies and in the United Kingdom, in 2010, 37% of 15‐ to 19‐year‐olds and 18% of those 20 to 24 years of age were entered onto clinical trials. However, enrollment rates varied by age, cancer types, and pathway of care, with higher rates of inclusion in adolescents versus young adults and in pediatric versus adult settings . When trials are available, access might vary according to centers; AYAs seen at a children's hospital are significantly more likely to enroll compared to AYAs seen at any of the primarily adult institutions .…”
Section: Discussionmentioning
confidence: 99%